Deep Metric Learning-Assisted 3D Audio-Visual Speaker Tracking via Two-Layer Particle Filter. (31st August 2020) - Li, Yidi; Liu, Hong; Yang, Bing; Ding, Runwei; Chen, Yang
Abstract : For speaker tracking, integrating multimodal information from audio and video provides an effective and promising solution. The current challenges are focused on the construction of a stable observation model. To this end, we propose a 3D audio-visual speaker tracker assisted by deep metric learning on the two-layer particle filter framework. Firstly, the audio-guided motion model is applied to generate candidate samples in the hierarchical structure consisting of an audio layer and a visual layer. Then, a stable observation model is proposed with a designed Siamese network, which provides the similarity-based likelihood to calculate particle weights. The speaker position is estimated using an optimal particle set, which integrates the decisions from audio particles and visual particles. Finally, the long short-term mechanism-based template update strategy is adopted to prevent drift during tracking. Experimental results demonstrate that the proposed method outperforms the single-modal trackers and comparison methods. Efficient and robust tracking is achieved both in 3D space and on image plane.